The impact of some quality standards on the satisfaction of students at Zarqa University in Jordan - Al - Momani, Rabi Fakhri Falah (Journal of Educational and Psychological Sciences, 2018)
The study aimed at revealing the effect of the quality of education on the satisfaction of students at Zarqa Private University. The researcher used the descriptive approach. In order to achieve the objective of the study, the researcher constructed a questionnaire addressed to the university students, which includes (30) parts divided into three dimensions: curriculum, services, The study concluded that the educational quality level was rated (high) with an average of (3.42 of 5). In terms of the dimensions of the study, , With an average of (3.71)). Then the services are averaged (3.53), both of which are rated (high), then the curriculum is averaged (3.40) and the estimate (average), The results also showed significant differences between the quality of education and the satisfaction of the students of Zarqa Private University, due to the gender variable and for females, and a positive relationship was found (0.705) between the quality of education and student satisfaction. A number of recommendations and proposals to raise the quality of services and increase the satisfaction of students, including: work on the quality of education from time to time to see the improvement in quality and to identify the obstacles that limit the provision of service to students, and the work of workshops and training courses for all students and staff at the University to learn about Quality and most important at the university.